Fishermen's location choice under spatio-temporal update of expectations. (September 2018) - Hutniczak, Barbara; Münch, Angela
Abstract: Information acquired by individuals over time plays a crucial role in their decision-making process. Gained experience updates beliefs on expected payoffs and is used in a range of decisions each individual is facing. In this paper, we focus on the formation of beliefs about the payoffs associated with spatial choices set in an uncertain environment. We task ourselves with better understanding of day-to-day flexibility of actions as a result of continuous update of prior expectations. We built a model where private and common knowledge on expected economic returns blend and lead to divergence of expectations between individuals. This innovation expands the frontiers of spatio-temporal modeling of micro-behavior to offer a new insight on decay of information relevance with increasing spatial and temporal separation. Application to fishermen harvest location choices demonstrates the use of the model. Successful fisheries management must be able to accurately predict the response of fishermen to regulations with particular attention paid to flexible technologies which allow individuals to adjust effort and alter behavior. Good understanding of fishing locations choice and location adjustment flexibility can contribute substantially to a design of management practices with spatial components.